Integrated use of geoelectrical imaging and hydrochemical methods in delineating limits of polluted surface and ground water at a landfill site in Ibadan area, Southwestern Nigeria (2001)
The Impact of solid waste disposal at the Ring Road district of Ibadan metropolis, southwestern Nigeria, on the adjoining surface and ground-water sources, has been Investigated. The basement rocks include Precambrian quartzites and quartz-schists that have been extensively weathered. In this study, the geophysical survey Involved 5 electrical imaging lines, while the hydrochemical database comprised 4 samples of surface water and 6 samples of groundwater from dug wells. The samples were analysed for turbidity, pH, conductivity, total hardness, total dissolved solids (TDS), alkalinity, Cl, No3, SO42, PO43, Na, K+, Mg2 and Fe2. The results show that water bodies located in a down gradient direction and in close vicinity of the landfill, has received significant inputs of inorganic pollutants. Statistical analyses indicate positive correlation (p<0.05) between the following pairs of parameters: Ca2 and Mg2. (R=0.83; Na+ and K+ (R=0.95); (Na2+Mg2) and Cl (R = 0.92); (Na2 + K2) and Ca2 (R=0.96); pH and Cr (R = 0.87). Moreover. the electrical conductivity shows a positive correlation (p<0.05) with the concentrations of K+ (R = 0.97); Na+ (R = 0.96); Ca2+ (R = 0.93); Mg2+ (R = 0.82); Fe2+ (R = 0.85); Cl (R = 0.91) and TDS (R = 0.98). On the other hand, the conductivity shows a negative correlation with SO42 (R = 0.78). Corroborating evidence was provided from the geoelectrical imaging data which Indicate that the thickness of the waste dump ranges between about 2m to 17m, while its resistivity is low at between 4 and 8ohm-m. The low resistivity is due to the presence of leachate emanating from the site and this has also polluted the surface and ground-waters in the Immediate delineation of the limits of the probable polluted zone.